Comparative study of transcriptome profiles of mechanical- and skin-transformed Schistosoma mansoni schistosomula. - Anna V Protasio; David W Dunne; Matthew Berriman (Public Library of Science (PLoS), 2013)
Schistosome infection begins with the penetration of cercariae through healthy unbroken host skin. This process leads to the transformation of the free-living larvae into obligate parasites called schistosomula. This irreversible transformation, which occurs in as little as two hours, involves casting the cercaria tail and complete remodelling of the surface membrane. At this stage, parasites are vulnerable to host immune attack and oxidative stress. Consequently, the mechanisms by which the parasite recognises and swiftly adapts to the human host are still the subject of many studies, especially in the context of development of intervention strategies against schistosomiasis infection. Because obtaining enough material from in vivo infections is not always feasible for such studies, the transformation process is often mimicked in the laboratory by application of shear pressure to a cercarial sample resulting in mechanically transformed (MT) schistosomula. These parasites share remarkable morphological and biochemical similarity to the naturally transformed counterparts and have been considered a good proxy for parasites undergoing natural infection. Relying on this equivalency, MT schistosomula have been used almost exclusively in high-throughput studies of gene expression, identification of drug targets and identification of effective drugs against schistosomes. However, the transcriptional equivalency between skin-transformed (ST) and MT schistosomula has never been proven. In our approach to compare these two types of schistosomula preparations and to explore differences in gene expression triggered by the presence of a skin barrier, we performed RNA-seq transcriptome profiling of ST and MT schistosomula at 24 hours post transformation. We report that these two very distinct schistosomula preparations differ only in the expression of 38 genes (out of ∼11,000), providing convincing evidence to resolve the skin vs. mechanical long-lasting controversy.